Retrieving Palaeoecological Information from Historic Fossil Finds: A Taphonomic Cold Case from Orciano Pisano (Central Italy) Reveals a Distinctive Trophic Interaction in the Pliocene Mediterranean Sea - Edoardo Terranova; Giovanni Bianucci; Marco Merella; Chiara Sorbini; Alberto Collareta (Journal of Marine Science and Engineering, 2025)
Evidence of trophic interactions between sharks and cetaceans is rather widespread in the fossil record, consisting as it does of tooth marks on bones and rarer teeth or tooth fragments embedded in (or associated with) skeletal remains. Here, we reappraise a partial mysticete (baleen whale) forelimb that was collected more than a century ago from Pliocene deposits exposed at the celebrated fossil locality of Orciano Pisano (Tuscany, central Italy). This specimen, which is revealed to originate from an early juvenile individual, features shark tooth marks on both the humerus and radius. Whether these traces are due to active predation or to scavenging cannot be ascertained. During the Pliocene, the Mediterranean Basin was inhabited by a diverse elasmobranch fauna, including a number of mammal-eating forms that no longer inhabit the Mediterranean Sea (e.g., Galeocerdo and some Carcharhinus spp. as well as the extinct Parotodus). Early juvenile mysticetes were also likely more common than today in the Pliocene Mediterranean Sea, which may have contained balaenid and balaenopterid calving grounds, thus providing the Mediterranean mammal-eating sharks with vulnerable, energetically valuable potential prey items. Thus, our results evoke a kind of trophic interaction that was likely common and ecologically relevant in the Pliocene Mediterranean Sea.